PENGEMBANGAN MEDIA PEMBELAJARAN DALAM BENTUK MACROMEDIA FLASH MATERI TABUNG UNTUK SMP KELAS IX - Khairani, Majidah; Febrinal, Dian (Jurnal Ipteks Terapan, 2016)
The purpose of the research is to produce media-based math learning macromedia flash on the subject of the cylinder in the junior class IX valid, practical and efective for her then experimented to see the potential effects of media-based learning macromedia flash cylinder subject to students understanding of concepts. The method used is the development of research that consists of three phases: define, design and develop. The material validation result 74,64 was in good. The media was tried out at SMPN 44 Sijunjung. The studentsâ response in small and large-scale try out result 87,56 were in very good category (very practical). Obtained from testing the potential effects of instructional media using macromedia flash to the understanding of the concept of students is 78 in both categories. It can be concluded that the macromedia flash media-based learning subject that researchers develop effective cilinder used in the learning of mathematics.